Are Japanese randomized controlled trials up to the task? A systematic review. - Daisuke Yoneoka; Akinori Hisashige; Erika Ota; Karin Miyamoto; Shuhei Nomura; Miwako Segawa; Stuart Gilmour; Kenji Shibuya (PLoS ONE)
Objectives Despite increasing numbers of RCTs done in Japan, existing international databases fail to capture them, and detailed information on the quality of Japanese RCTs is still missing. This study assessed the characteristics and quality of Japanese RCTs and analyzed factors related to their quality. Methods All RCTs conducted in Japan, and published as original articles that assessed the effect of healthcare interventions on humans in 2010, were included. We excluded study protocols, conference abstracts, and comments. In addition, quasi-RCTs were excluded. Data were independently abstracted and assessed by two of the authors and disagreements were resolved by consensus. The quality of Japanese RCTs randomly sampled was assessed using the method guidelines for systematic reviews from the Cochrane Back Review Group. The factors affecting RCT quality were analyzed using a logistic regression model. Results A total of 1013 RCTs conducted in Japan were published in 2010. The majority was small-scale (55% of RCTs with sample size less than 50). Eighty percent of RCTs had no information on the funding source and only 8% had been registered before their implementation. RCTs not indexed in international databases were a moderate number (118 RCTs: 37.7% of non-indexed RCTs were of high quality). Surgical intervention studies for external causes of morbidity and mortality with a large sample size, trial registration and a large number of arms were most likely to be of higher quality. Conclusion Despite a considerable number of RCTs conducted in Japan, their quality is not satisfactory in some domains. On the other hand, there are high-quality, non-indexed RCTs. The full disclosure of trial information and quality control of clinical trials are urgently needed in Japan.